Strategi Transformasi Tata Kelola Pegawai Pemerintah Non Pegawai Negeri Sipil (PPNPN) di Unit Pelaksana Teknis Puskesmas Dinas Kesehatan Kota Bandung - Anhar Hadian; Deddy Mulyadi; Nita Nurliawati (Jurnal Media Administrasi Terapan, 2023)
Problems in Bandung city health departement related to Government Regulation Number 49 of 2018 clause 99 need to be addressed cerafully because it will reduce the number of human resources in the Health Office, especially human resources in the Puskesmas. This study aims to analyze the implementation of PPNPN governance at the Bandung City Health office and formulate a new strategy. This study used a qualitative, data collection use interviews and documentation studies with analysis technique use SWOT analysis. Based on the results of the study, it was found that the there were obstacles in the implementation of PPNPN governance, including the legal rules for PPNPN to get the status of being a PPPK or civil servants who have not been in favor of PPNPN because the current rules have not considered the period of service and work experience of PPNPN. PPNPN does not have a career development concept. PPNPN does not yet have standard rules in the management of performance appraisal. Performance appraisal given to PPNPN is still subjective. Therefore, the authors propose a PPNP governance strategy that can be applied to the implementation of PPNPN governance at the Bandung City Service. The strategy offered by the researcher is the Renewal strategy by Providing Incentives for PPNPN. Proposing PPNPN career development with achievements in reframing, revitalization, renewel, PPNPN governance with the proposed standard rules for PPNPN related to performance appraisal and discipline enforcement. Selection of PPNPN to be able to become PPPK or PNS.